ALIMENTATION PRÉCOCE AUX PRODUITS DE MANIOC AMER ET TROUBLES DU DÉVELOPPEMENT MOTEUR CHEZ L’ENFANT DE 11 À 59 MOIS À KAHEMBA, MILIEU AFFECTÉ PAR LE KONZO - Md , Kisioko Katunda Elyse; Md , Yatwa Zaniwe Roger Venant; Md , Sombo Safi Ayanne Marie-Therese; Md , Mishika Mukania Jeannette; Md , Mukeba Kahamba Daniel Lord; Md , Mbusa Kombi Justin; Md , Tshala Katumbay Desire; Md , Okitundu Luwa E-Andjafono Daniel (IJRDO - Journal of Social Science and Humanities Research, 2022)
In Kahemba, young children are exposed at an early age to cyanogenic products of dietary origin through the consumption of poorly detoxified bitter cassava. This cyanide intoxication is responsible for motor development disorders in these children. It seems important to know the age of onset of consumption of bitter cassava products and the relationship between motor development disorders and early feeding with these products.This exploratory study was conducted to determine the relationship between early consumption of bitter cassava products and motor development disorders in children in Kahemba, a konzo endemic area in the Democratic Republic of Congo.METHODS: This cross-sectional study was undertaken from July 15 to August 5, 2016, among 50 children aged 11 to 59 months from 46 consenting study households.  The primary variables of interest were the characteristics of the children's feeding of bitter cassava products, nutritional status, and motor development.Results: Children ranged in age from 13 to 59 months, with a M/F sex ratio of 1.5;   Bitter cassava products were consumed before the age of 6 months in 88% of the cases and in 64% without mixing with corn, in 64.3% of the cases the cassava was retted in the home containers, spastic paraparesis was noted in 34% (p=0.034), Abnormal walking on all fours after 18 months of age 16% (p<0.001), spastic scissors walking 26% (p<0.001), imbalance in standing 34% (p=0.034), tremor in the execution of the movement 26% (p<0.001). The 94.1% of children with spastic paraparesis, the 92.3% with tremor, the 100% with four-legged movement beyond 18 months and the 92.3% with spastic scissor walking were fed with cassava products alone without corn mixture (p<0.001) ; Spastic paraparesis was linked in 80% to the rolling of cassava in the home bins, in 88.2% to the consumption of bitter cassava before the age of 6 months, as well as 92.3% for tremor and 100% for abnormal crawling beyond 18 months. Malnutrition was noted in 100% of children who had never stood up, in 100% of those with abnormal crawling beyond 18 months and in 84.6% with spastic scissor walking. Conclusion: In the city of Kahemba, an environment endemic to Konzo, children who were fed bitter cassava products at an early age and who were not sufficiently detoxified showed motor development disorders that would prelude the onset of Konzo in these children. This would have a negative impact on the socio-economic future of the territory of KAHEMBA in particular and that of the Democratic Republic of Congo in general.Preventive measures for psychomotor disorders in children in these environments should take this situation into account.